Kenneth A. Kitchen and Paul J. N. Lawrence, Treaty, Law and Covenant in the Ancient Near East, 3 volumes, Wiesbaden: Harrassowitz Verlag, 2012, 1641 pp. + lxxxiv, 1641, 7 charts, ISBN: 978-3-447-06726-3, €289.00. - Siddall, Luis R. (Buried History: The Journal of the Australian Institute of Archaeology, 2016)
None